The relationship between the curriculum design of the major in modern languages with a specialty in english and french that the University of El Salvador Offers and the labour market requirements in the city of San Salvador - Canizález Canizález, Cristobal Alexander
This graduation project contains the most relevant information about the relationship between the curriculum of the Major in Modern Languages from the University of El Salvador and its design and the job market demands and requirements of employees in the San Salvador area. The information contains the General and Specific Objectives that this research intends to reach, the Research Questions, the Description and Justification that refers to the explanation of the purpose of the study, the Theoretical Framework, the method applied to develop the analysis as well as the instruments used to gather information from the selected sample, the questionnaire is organized in graphics that show the students´ opinions an analysis of these results, some conclusions and recommendations that help this project elaboration. Three variables came into consideration when the research was carried out: the curricular design of the major in question, the job market requirements and demands; and the opinion of students selected between these two factors. Here are the results found after the interviews to the companies, the students and the study of the program as well as the conclusions and suggestions.